Super-spreading social events for COVID-19 transmission: evidence from the investigation of six early clusters in Bahrain - Alsayyad, Adel; Chlif, Sadok; Mohamed, Afaf; Habbash, Fatema; Ayoob, Zahra; Almarabheh, Amer; Al Sayed, Kubra; Alsaleh, Aseel; Alhajeri, Maryam; Alzayani, Salman; Abu Alfatah, Najat; Ahmed, Jamil; et al. (Frontiers in Public Health, 2023)
Introduction This study aimed to characterize six early clusters of COVID-19 and derive key transmission parameters from confirmed cases that were traced between April and June 2020 in Bahrain. Methods Pairs of “infector-infectee” allowed us to map the clusters and estimate the incubation period serial interval as the secondary attack rate. The chi-squared test, with a p-value computed using the Monte Carlo test, measured associations between categorical variables. Statistical analysis was performed using R software and the “data.tree, tidyverse” libraries. Results From 9 April to 27 June 2020, we investigated 596 individuals suspected of COVID-19, of whom 127 positive cases were confirmed by PCR and linked in six clusters. The mean age was 30.34 years (S.D. = 17.84 years). The male-to-female ratio was 0.87 (276/318), and most of the contacts were of Bahraini citizenship (511/591 = 86.5%). Exposure occurred within the family in 74.3% (411/553), and 18.9% of clusters' cases were symptomatic (23/122 = 18.9%). Mapped clusters and generations increased after 24 May 2020, corresponding to “Aid El-Fitr.” The mean incubation period was 4 days, and the mean serial interval ranged from 3 to 3.31 days. The secondary attack rate was 0.21 (95% C.I.) = [0.17–0.24]. Conclusion COVID-19 transmission was amplified due to the high number of families mixing during “Aid El Fitr” and “Ramadhan,” generating important clusters. Estimated serial intervals and incubation periods support asymptomatic transmission.